Site-Specific Volumetric Skeletal Changes in Women with a Distal Forearm Fracture. (30th September 2021) - Wihlborg, Axel; Bergström, Karin; Bergström, Ingrid; Gerdhem, Paul
Abstract : Purpose . To assess site-specific volumetric bone and muscle changes, as well as demographic and biochemical changes, in postmenopausal women with a low-energy distal forearm fracture. Methods . In a cross-sectional case-control study, postmenopausal women with a distal forearm fracture were compared with age- and gender-matched controls. In total, 203 postmenopausal women (104 cases and 99 controls), with a mean age of 65 years, were included. Measurements included peripheral quantitative computed tomography (pQCT) and dual-energy X-ray absorptiometry (DXA) as well as blood sampling and questionnaires. Results . Forearm trabecular volumetric BMD and total BMD assessed with pQCT were significantly lower in fracture cases compared to controls (p < 0.001 ). Significantly higher cross-sectional area, lower cortical BMD, and lower cortical thickness were seen in women with fracture (p < 0.033, p < 0.001, and p < 0.001, respectively). Postmenopausal women with fracture had significantly lower hip and spine areal BMD assessed with DXA (p < 0.001 ). Activity level was higher and a history of falling was more frequent in women with fracture (p < 0.019 and p < 0.001, respectively). Vertebral fracture was observed in 24 women (22%) with a distal forearm fracture. Muscle area, muscle density, PTH, and 25OHD did not differ between fracture cases and controls. Conclusion . A distal forearm fracture was associated with site-specific and central bone changes. Postmenopausal women with fracture had a larger bone area in combination with a thinner cortex and lower site-specific total BMD. In addition, women with fracture had a higher activity level, an increased occurrence of previous fall accidents, and a high prevalence of vertebral fractures. Forearm muscle composition, PTH, and 25OHD were not associated with forearm fracture. Fracture preventive measures following a low-energy distal forearm fracture seem beneficial.